The Results of Evaluation Online Learning Using Hypnoteaching Method and Self-hypnosis - Wita Asmalinda; Yunetra Franciska; Edy Sapada (Universitas Aisyah Pringsewu, 2023)
Hypnoteaching is a method that is attractive, provides comfort, and makes students feel happy when participating in the online learning process. This study aimed to determine the effect of online learning using hypnoteaching and self-hypnosis on the results of student learning evaluation. This type of research is quasi-experimental with a comparison group (post-test only with control group design) for 2 months. The research sample was all students in the Diploma III midwifery program, totaling 87 people. Data analysis was a significant difference in the mean value of learning evaluation results in the treatment group and the control group, it was concluded that the hypnoteaching and self-hypnosis methods were effective in improving student learning evaluation results. It is advisable to conduct research with learning motivation variables and measurement of brain waves.